2022
DOI: 10.2147/dddt.s351264
|View full text |Cite
|
Sign up to set email alerts
|

Mahuang Decoction Attenuates Airway Inflammation and Remodeling in Asthma via Suppression of the SP1/FGFR3/PI3K/AKT Axis

Abstract: Background/Purpose Mahuang decoction (MHD) is a classic famous traditional Chinese medicine and has various pharmacological effects, including anti-inflammation and anti-asthma. In this study, we aimed to investigate the potential protective effect of MHD against asthma and elucidated the underlying mechanism. Materials and Methods A mouse model of asthma was induced by ovalbumin (OVA) treatment, and then treated with MHD to evaluate its effect on the asthma. Gain- or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition to bronchodilation, ASMCs are also recognized as attractive anti-inflammatory targets for treating chronic asthma because they are known to release cytokines that play a key role in orchestrating and perpetuating airway inflammation 65 . For example, OVA-treated mice exhibit increased level of inflammatory cytokines including IL-4, IL-6 and TNF-α in the BALF, which can be inhibited by anti-inflammatory mahuang decoction, and patients with severe asthma have recently been approved to be treated by blocking antibodies against specific cytokines 66 , 67 . Consistent with these findings, our results demonstrated that FFA significantly attenuated the mRNA expression of inflammatory cytokines released from LPS-stimulated ASMCs, including IL-1β, IL-2, IL-6, IP-10, MCP-1, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bronchodilation, ASMCs are also recognized as attractive anti-inflammatory targets for treating chronic asthma because they are known to release cytokines that play a key role in orchestrating and perpetuating airway inflammation 65 . For example, OVA-treated mice exhibit increased level of inflammatory cytokines including IL-4, IL-6 and TNF-α in the BALF, which can be inhibited by anti-inflammatory mahuang decoction, and patients with severe asthma have recently been approved to be treated by blocking antibodies against specific cytokines 66 , 67 . Consistent with these findings, our results demonstrated that FFA significantly attenuated the mRNA expression of inflammatory cytokines released from LPS-stimulated ASMCs, including IL-1β, IL-2, IL-6, IP-10, MCP-1, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products exhibit the complex chemical backbone and the rich functionalization, making them unique biological activity and unique properties that cannot be replaced as lead compounds in pharmaceutical research [34][35][36][37]. Many antiasthmatic drugs derived from the herbal medicine, such as ephedrine and glycyrrhizic acid, have been used widely in the clinic for prevention and treatment of airway infammation and asthma [38][39][40][41]. Given the diversity of the compounds in the plant extract, network pharmacology technology was employed to fnd the potential active compounds in HHAE which may be responsible for its therapeutic efects against OVA-induced asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests the key role of the PI3K/Akt pathway in the immune response and remodelling in the airways, contributing to the pathological changes of asthma (Wei et al. 2022 ). In this respect, it has been reported that inhibiting the PI3K/Akt pathway by Akt dephosphorylation could reduce the expression of hypoxia-inducing factor HIF-α and vascular endothelial growth factor VEGF, thereby reducing the permeability of respiratory mucosa, inhibiting respiratory oedema and contraction, and reducing airway remodelling in asthma (Dahlin et al.…”
Section: Introductionmentioning
confidence: 99%